On the Geometric Modelling of the Energy of Quasi Magnetic Curves - Körpınar, Talat; Demirkol, Rıdvan Cem (AMER SCIENTIFIC PUBLISHERS, 2018)
In this study, we firstly characterize quasi magnetic curves and associated magnetic fields by considering the evolution of the charged particle together with its quasi frame construction. Then, we compute the energy of each quasi magnetic curve in terms of its principal curvatures. Finally, we determine the ratio of charge to mass, the radius of gyration and the gyro-frequency of quasi magnetic curves to investigate the exact movement of charged particles in a given uniform magnetic field in the ordinary space.
Keywords: Magnetic Field; Force Field; Quasi Frame; Magnetic Curve; Energy; Magnetic Force